Leveraging data and policy interventions to strengthen tobacco control in the Eastern Mediterranean Region - Saad, Randa K.; Mostafa, Nayera S.; Nabulsi, Mahmoud; Al-Saket, Sarah; Nemer, Maysaa; Obeidat, Nour; Khader, Yousef (Frontiers in Public Health, 2025)
The “Utilizing Tobacco Control Evidence to Inform Policies and Programs” workshop focused on supporting Eastern Mediterranean Region (EMR) countries facing tobacco control challenges and seeking evidence-based mechanisms within the WHO MPOWER framework to strengthen tobacco control efforts. Participants from Egypt, Iraq, Jordan, Lebanon, and Palestine reviewed their tobacco control policies, identified barriers, and proposed countermeasures. Key challenges included weak enforcement of smoke-free laws and frequent violations due to an insufficient task force to monitor and ensure compliance with regulations. Even when violations are detected, penalties are low and often appealed. Inadequate data collection hinders evidence-based interventions and the ability to track the spread and emergence of tobacco and vaping products, such as waterpipes and, more recently, electronic cigarettes and heat-not-burn tobacco products. Tobacco industry interference further weakens political will and hampers policy enforcement. The rise of novel tobacco products adds regulatory complexities to laws with pre-existing loopholes. Workshop participants recommended increasing tobacco taxes in Iraq and Egypt to reduce tobacco accessibility. Expanding cessation services in public health facilities, particularly in Jordan and Palestine, was also recommended, along with public awareness campaigns to promote quitting. Improving tobacco surveillance, especially in Iraq, through tools like the Global Tobacco Surveillance System, was highlighted to enhance data collection and inform policies. Strengthening enforcement mechanisms, increasing fines, and improving coordination between public health and law enforcement were identified as critical measures for improving smoke-free policy compliance.